A bridge reinforcement mixed gel containing carbon fiber and preparation method thereof
By developing a mixed gel material containing carbon fiber, the existing cement-based reinforcement materials have been solved, and the effective bridge reinforcement effect has been achieved.
Patent Information
- Application Number
- CN202411284261.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing cement-based reinforcement materials have high cost, low bonding strength and poor compressive strength, which limit the effect of concrete structure reinforcement.
A bridge reinforced carbon fiber hybrid gel is developed, with components including gel substrates, fine aggregates, coarse aggregates, reinforced fibers, aluminum borate whiskers and nano-calcium carbonate, and the gel material is prepared by specific proportions and process steps.
The compressive strength and bonding strength of the gel material are improved, production costs are reduced, waste reuse is achieved, and the bridge reinforcement effect is enhanced.
Smart Images

Figure CN119191770B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building gel materials, in particular to a bridge reinforcement carbon fiber-containing mixed gel and a preparation method thereof. Background Art
[0002] In recent years, with the increase in bridge spans, the quality requirements for large-volume concrete structures such as abutments and tower bases have become increasingly stringent. However, due to the large cross-sectional size of large-volume concrete, the hydration reaction of cement will generate a large amount of hydration heat during the construction process. Concrete is a poor conductor of heat, and heat is accumulated inside and is not easy to dissipate, while the surface dissipates heat quickly, which forms a large temperature difference between the interior and surface of the concrete, resulting in uneven temperature deformation and temperature stress. Once the tensile stress exceeds the instantaneous tensile strength of the concrete, thermal cracks or through cracks will occur inside or on the surface of the concrete. The appearance of cracks not only affects the appearance quality of the structure, but more importantly, it will destroy the integrity and stability of the structure, and in severe cases, it will cause the structure to be unable to be used normally. Therefore, in order to prevent serious damage to the bridge, it is necessary to transform and reinforce it.
[0003] Concrete structure reinforcement materials mainly include cement-based reinforcement materials, steel and welding materials, fibers and fiber composite materials, adhesives and rust inhibitors, among which cement-based reinforcement materials, i.e., cementitious materials, are the most widely used. Traditional cement-based reinforcement materials have some problems: (1) Most of them use non-renewable natural resources, and the range of material selection is narrow; (2) The reinforcement and maintenance cycle is long, the bonding strength between new and old concrete is low, and the compressive strength is poor; these problems make the material cost of concrete structure reinforcement high, the overall cost is high, and the effect of concrete reinforcement is limited, which in turn has an adverse effect on the reinforcement of bridges.
[0004] Therefore, developing a gel material with low cost, high bonding strength and good compressive strength is beneficial to improving the reinforcement effect of bridges. Summary of the invention
[0005] The purpose of the present invention is to provide a bridge reinforcement containing carbon fiber mixed gel and a preparation method thereof, which solves the problems of high cost, low bonding strength and poor compressive strength of cement-based reinforcement materials in the prior art.
[0006] To achieve the above object, the present invention provides a bridge reinforcement carbon fiber mixed gel, which comprises the following components by weight: 30-100 parts of gel matrix, 5-10 parts of fine aggregate, 5-15 parts of coarse aggregate, 0.5-1 parts of reinforcing fiber, 0.03-0.04 parts of aluminum borate whisker, 0.1-0.2 parts of nano calcium carbonate, and 20-40 parts of water;
[0007] The gel matrix includes carbide slag, bentonite and metakaolin, and the mass ratio of carbide slag, bentonite and metakaolin is (1-3): (1-3): (1-4). The carbide slag is the sediment after the carbide slag slurry of the chlor-alkali plant is placed.
[0008] Preferably, the particle size of the fine aggregate is 30-50 μm, and the fine aggregate includes recycled construction waste powder and recycled glass powder.
[0009] Preferably, the particle size of the coarse aggregate is 0.15-5.00 mm, and the coarse aggregate is natural river sand.
[0010] Preferably, the reinforcing fibers include carbon fibers with lengths of 12-15 mm, 6-10 mm, and 2-5 mm, respectively, and the mass ratio of carbon fibers of different lengths is (2-3):(1-2):(0.1-1.5). Fibers of different lengths can span cracks in the matrix, hindering their development, thereby achieving the purpose of crack resistance and reinforcement.
[0011] Preferably, the carbide slag comprises the following components by weight: 50-60 parts of CaO, 7-10 parts of SiO2, 1-2 parts of Al2O3, 2-10 parts of Fe2O3, 5-7 parts of MgO, 0.3-0.7 parts of Na2SiO3, 0.05-0.1 parts of Na2CO3, and 0.2-0.4 parts of NaCl.
[0012] Preferably, the metakaolin comprises the following components by weight: 50-65 parts of SiO2 and 40-60 parts of Al2O3.
[0013] A method for preparing a bridge reinforcement mixed gel containing carbon fibers, comprising the following steps:
[0014] (1) weighing carbide slag, bentonite, metakaolin and water in proportion, adding them into a mixer, stirring, and mixing evenly to obtain a mixture A;
[0015] (2) adding aluminum borate whiskers and nano-calcium carbonate to mixed material A, and stirring to obtain mixed material B;
[0016] (3) Add fine aggregate, coarse aggregate and reinforcing fiber to mixture B and stir at high speed to obtain a mixed gel.
[0017] Preferably, in step (1), the stirring time is 1-3 min, and the stirring rate is 30-50 r / min.
[0018] Preferably, in step (2), the stirring time is 0.5-2 min, and the stirring rate is 30-50 r / min.
[0019] Preferably, in step (3), the stirring time is 1-2 min, and the stirring rate is 120-160 r / min.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention utilizes the key alkaline components contained in carbide slag as a spent alkali activator to fully induce the activation of the alkali-activated clay, which can quickly hydrate and polycondense to form a gel structure composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons, thereby increasing the amount of hydrated calcium silicate / hydrated calcium aluminosilicate gel, greatly improving the density of the composite gel, and improving the compressive strength of the system, thereby fully utilizing the spent alkali and effectively reducing the production cost of alkali-activated gelling materials.
[0022] (2) The nano calcium carbonate used in the present invention is a nano-scale reinforcing material, which promotes the development of early strength of concrete through its nano effect and the synergistic effect of aluminum borate whiskers, and has a certain water-reducing and reinforcing effect. In addition, aluminum borate whiskers have excellent mechanical properties, small size, and good dispersibility in the system. When the strength of the gel material matrix is formed, the density and later strength of the gel can be increased through microscopic reinforcement.
[0023] (3) In the present invention, carbon fiber is used as reinforcing fiber, which can not only play a role in strengthening the skeleton, but also improve the occurrence of agglomeration between base materials during the mixing process. Fibers of different lengths can span the cracks of the matrix, hindering their development, thereby achieving the purpose of crack resistance and reinforcement.
[0024] (4) In the present invention, bentonite is dispersed in water to form a colloidal suspension, which increases the viscosity of the system. At the same time, fine aggregate is also dispersed in the colloidal suspension, which improves the structural strength, uniformity and density of the bentonite, and can effectively improve the consistency of the gel material, thereby improving the bonding strength of the material. It is then mixed with the coarse aggregate. Since the bentonite has a certain viscosity, the separation of the coarse aggregate is reduced, thereby improving the compressive strength of the gel material.
[0025] (5) The present invention utilizes recycled construction waste powder and recycled glass powder as fine aggregate. The recycled construction waste powder and recycled glass powder can be obtained locally and have low processing costs. The carbide slag is the sediment left after the carbide slurry of the chlor-alkali plant is placed, thereby realizing the recycling of waste. That is, the present invention meets the trend of recycling construction waste, domestic waste and factory production waste, and solves the problem of environmental pollution.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart of a method for preparing a bridge reinforcement mixed gel containing carbon fibers. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0029] The present invention provides a bridge reinforcement carbon fiber mixed gel, which comprises the following components by weight: 30-100 parts of gel base material, 5-10 parts of fine aggregate, 5-15 parts of coarse aggregate, 0.5-1 parts of reinforcing fiber, 0.03-0.04 parts of aluminum borate whisker, 0.1-0.2 parts of nano calcium carbonate, and 20-40 parts of water. The present invention controls the weight ratio of each component within the above range, ensures the compressive strength of the prepared mixed gel, and at the same time makes it have good fluidity and working performance.
[0030] The gel matrix includes carbide slag, bentonite and metakaolin. In the present invention, the mass ratio of carbide slag, bentonite and metakaolin is preferably (1-3): (1-3): (1-4), and the carbide slag is the sediment after the carbide slag slurry of the chlor-alkali plant is placed. The present invention controls the mass ratio of carbide slag, bentonite and metakaolin within the above range, so as to fully stimulate the metakaolin by controlling the alkaline component, so as to make full use of each phase material in the subsequent hydration reaction process, thereby ensuring the density and compressive strength of the mixed gel.
[0031] In the present invention, the particle size of the fine aggregate is preferably 30-50 μm, and the fine aggregate includes recycled construction waste powder and recycled glass powder. Recycled construction waste powder and recycled glass powder can be obtained locally, and the processing cost is low, which realizes the recycling of waste and reduces production costs. The present invention controls the particle size of the fine aggregate within the above range to provide smaller particles for the mixed gel, thereby improving the matching degree of each component particle in the mixed gel material. The better the matching degree, the more free water there is between the particles. Sufficient free water can improve the fluidity between the particles during the molding process of the mixed gel material, which is beneficial to reduce the porosity and thus improve the compressive strength of the mixed gel material.
[0032] In the present invention, the particle size of the coarse aggregate is preferably 0.15-5.00 mm, and the coarse aggregate is natural river sand. The present invention provides medium-sized particles for the mixed gel by controlling the particle size of the coarse aggregate within the above range, so that the structure is more compact, and each phase forms a unified whole, thereby improving the compressive strength and durability of the mixed gel material, improving the fluidity between particles during the molding process of the mixed gel material and reducing shrinkage, thereby reducing the risk of cracking.
[0033] In the present invention, the reinforcing fibers include carbon fibers with lengths of 12-15 mm, 6-10 mm, and 2-5 mm, respectively, and the mass ratio of the carbon fibers of each length is (2-3):(1-2):(0.1-1.5). Fibers of different lengths can span the cracks of the matrix, hindering their development, thereby achieving the purpose of crack resistance and reinforcement.
[0034] In the present invention, the carbide slag comprises the following components by weight: 50-60 parts of CaO, 7-10 parts of SiO2, 1-2 parts of Al2O3, 2-10 parts of Fe2O3, 5-7 parts of MgO, 0.3-0.7 parts of Na2SiO3, 0.05-0.1 parts of Na2CO3, and 0.2-0.4 parts of NaCl.
[0035] In the present invention, the metakaolin comprises the following components by weight: 50-65 parts of SiO2 and 40-60 parts of Al2O3.
[0036] A method for preparing a bridge reinforcement mixed gel containing carbon fibers, comprising the following steps:
[0037] (1) weighing carbide slag, bentonite, metakaolin and water in proportion, adding them into a mixer, stirring, and mixing evenly to obtain a mixture A;
[0038] (2) adding aluminum borate whiskers and nano-calcium carbonate to mixed material A, and stirring to obtain mixed material B;
[0039] (3) Add fine aggregate, coarse aggregate and reinforcing fiber to mixture B and stir at high speed to obtain a mixed gel.
[0040] In the present invention, the stirring time in step (1) is preferably 1-3 min, and the stirring rate is preferably 30-50 r / min. In the present invention, the stirring time and stirring rate are controlled within the above ranges to promote complete mixing of the components.
[0041] In the present invention, the stirring time in step (2) is preferably 0.5-2 min, and the stirring rate is preferably 30-50 r / min.
[0042] In the present invention, the stirring time in step (3) is preferably 1-2 min, and the stirring rate is preferably 120-160 r / min. The present invention controls the high stirring time and stirring rate within the above range to improve the uniformity and quality of the material.
[0043] The compositions of carbide slag, metakaolin, fine aggregate and reinforcing fiber used in Examples 1-3 are shown in Tables 1-4, and the particle size of the fine aggregate is in the range of 30-50 μm, and the particle size of the coarse aggregate is in the range of 2-5 mm.
[0044] Table 1 Composition statistics of carbide slag
[0045]
[0046] Table 2 Composition statistics of metakaolin
[0047] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> Mass fraction 62.5 45.8
[0048] Table 3 Composition statistics of fine aggregate
[0049] Element Recycled construction waste powder Recycled glass powder Mass fraction 50 50
[0050] Table 4 Composition statistics of reinforcing fibers
[0051] Fiber length 12-15mm 6-10mm 2-5mm Mass fraction 2.5 1.5 0.8
[0052] Example 1
[0053] A bridge reinforcement carbon fiber mixed gel, comprising the following components by weight:
[0054] 30 parts of adhesive base material, 5 parts of fine aggregate, 5 parts of coarse aggregate, 0.5 parts of reinforcing fiber, 0.03 parts of aluminum borate whisker, 0.1 parts of nano calcium carbonate, and 20 parts of water.
[0055] The gel matrix includes carbide slag, bentonite and metakaolin, and the mass ratio of carbide slag, bentonite and metakaolin is 1:1:1.
[0056] Example 2
[0057] A bridge reinforcement carbon fiber mixed gel comprises the following components by weight: 40 parts of gel base material, 6 parts of fine aggregate, 8 parts of coarse aggregate, 0.6 parts of reinforcing fiber, 0.03 parts of aluminum borate whisker, 0.12 parts of nano calcium carbonate and 25 parts of water.
[0058] The gel matrix includes carbide slag, bentonite and metakaolin, and the mass ratio of carbide slag, bentonite and metakaolin is 1:1:1.
[0059] Example 3
[0060] A bridge reinforcement carbon fiber mixed gel comprises the following components by weight: 60 parts of gel base material, 7 parts of fine aggregate, 10 parts of coarse aggregate, 0.75 parts of reinforcing fiber, 0.03 parts of aluminum borate whisker, 0.15 parts of nano calcium carbonate and 30 parts of water.
[0061] The gel matrix includes carbide slag, bentonite and metakaolin, and the mass ratio of carbide slag, bentonite and metakaolin is 1.5:1.5:2.
[0062] Example 4
[0063] A bridge reinforcement carbon fiber mixed gel comprises the following components by weight: 80 parts of gel base material, 8 parts of fine aggregate, 12 parts of coarse aggregate, 0.8 parts of reinforcing fiber, 0.03 parts of aluminum borate whisker, 0.15 parts of nano calcium carbonate and 35 parts of water.
[0064] The gel matrix includes carbide slag, bentonite and metakaolin, and the mass ratio of carbide slag, bentonite and metakaolin is 1.5:1.5:2.
[0065] Example 5
[0066] A bridge reinforcement carbon fiber mixed gel comprises the following components by weight: 100 parts of gel base material, 10 parts of fine aggregate, 15 parts of coarse aggregate, 1 part of reinforcing fiber, 0.04 parts of aluminum borate whisker, 0.2 parts of nano calcium carbonate and 40 parts of water.
[0067] The gel matrix includes carbide slag, bentonite and metakaolin, and the mass ratio of carbide slag, bentonite and metakaolin is 3:3:4.
[0068] Example 6
[0069] Figure 1 The flowchart of the preparation method of a bridge reinforcement mixed gel containing carbon fibers of the present invention is shown in the figure. The preparation method of a bridge reinforcement mixed gel containing carbon fibers of the present invention comprises the following steps:
[0070] (1) weighing carbide slag, bentonite, and metakaolin in a mass ratio of 1.5:1.5:2, mixing them to obtain a gel base material, then weighing 60 parts of the gel base material and 30 parts of water, adding them into a mixer, stirring, and mixing evenly to obtain a mixture A;
[0071] (2) adding 0.03 parts of aluminum borate whiskers and 0.15 parts of nano-calcium carbonate to mixed material A, and stirring evenly to obtain mixed material B;
[0072] (3) Add 7 parts of fine aggregate, 10 parts of coarse aggregate and 0.75 parts of reinforcing fiber to mixture B and stir at high speed to obtain a mixed gel.
[0073] The mixed gels prepared in Examples 1-5 were made into test pieces and tested for 7d and 28d compressive strength. The test results are shown in Table 5.
[0074] Specimen preparation: First, pour the mixed gel to fill 1 / 3 of the mold capacity, vibrate, then pour 1 / 3 of the mold capacity of the mixed gel, vibrate, and finally pour 1 / 3 of the mold capacity of the mixed gel, vibrate and shape, and then obtain the molded specimen. Then perform curing: After 24 hours, the specimen is demolded, and then under standard curing conditions, that is, temperature 20±2℃, relative humidity above 95%, the specimen is cured for 7d and 28d respectively, and then monitored.
[0075] Table 5 Statistics of strength test of mixed gel of Examples 1-5
[0076]
[0077]
[0078] As shown in Table 5, the 7d compressive strength of the mixed gels prepared in Examples 1-5 all reached above 26 MPa, and the 28d compressive strength all reached above 27 MPa, with high compressive strength, high comprehensive mechanical properties, and small performance differences.
[0079] The samples prepared in Examples 1-5 were placed in a constant temperature and humidity tester, set at an ambient temperature of 60°C and a humidity of 98% for 21 days, and then used in an electronic universal testing machine to uniformly stretch the samples at a test rate of 2 mm / min until they broke, to measure the bonding strength. The results are shown in Table 6.
[0080] Table 6 Bonding strength of mixed gels of Examples 1-5 under constant temperature and humidity conditions
[0081] Bond strength (MPa) Adhesive layer fracture Example 1 3.76 Unbroken Example 2 3.82 Unbroken Example 3 4.21 Unbroken Example 4 4.06 Unbroken Example 5 3.93 Unbroken
[0082] The samples prepared in Examples 1-5 were placed in a high and low temperature test chamber to perform a hot and cold cycle. Specifically, one cycle was 12 hours in a 70°C environment and 12 hours in a -5°C environment. After 15 cycles, the samples were uniformly stretched in an electronic universal testing machine at a test rate of 2 mm / min until they broke, and the bonding strength was measured. The results are shown in Table 7.
[0083] Table 7 Bond strength of mixed gels of Examples 1-5 under hot and cold cycle conditions
[0084]
[0085]
[0086] It can be seen from Tables 6 and 7 that the mixed gels prepared in Examples 1 to 5 have good bonding strength under constant temperature and humidity conditions and under hot and cold cycle conditions.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A bridge reinforcement containing carbon fiber hybrid gel, characterized in that: The composition includes the following components by weight: 30-100 parts of gel base material, 5-10 parts of fine aggregate, 5-15 parts of coarse aggregate, 0.5-1 parts of reinforcing fiber, 0.03-0.04 parts of aluminum borate whisker, 0.1-0.2 parts of nano calcium carbonate, and 20-40 parts of water; The gel matrix includes carbide slag, bentonite and metakaolin, and the mass ratio of carbide slag, bentonite and metakaolin is (1-3): (1-3): (1-4), the carbide slag is the sediment after the carbide slag slurry of the chlor-alkali plant is placed; the carbide slag includes the following components by weight: 50-60 parts of CaO, 7-10 parts of SiO2, 1-2 parts of Al2O3, 2-10 parts of Fe2O3, 5-7 parts of MgO, 0.3-0.7 parts of Na2SiO3, 0.05-0.1 parts of Na2CO3, and 0.2-0.4 parts of NaCl; Fine aggregate includes recycled construction waste powder and recycled glass powder; coarse aggregate is natural river sand; The reinforcing fibers include carbon fibers with lengths of 12-15 mm, 6-10 mm, and 2-5 mm, respectively, and the mass ratio of the carbon fibers of various lengths is (2-3):(1-2):(0.1-1.5).
2. The carbon fiber-containing hybrid gel for bridge reinforcement according to claim 1, characterized in that: The particle size of fine aggregate is 30-50μm.
3. The carbon fiber-containing hybrid gel for bridge reinforcement according to claim 1, characterized in that: The particle size of coarse aggregate is 0.15-5.00mm.
4. The carbon fiber-containing hybrid gel for bridge reinforcement according to claim 1, characterized in that: The metakaolin comprises the following components by weight: 50-65 parts of SiO2 and 40-60 parts of Al2O3.
5. A method for preparing a bridge reinforcement carbon fiber-containing hybrid gel as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: (1) weighing carbide slag, bentonite, metakaolin and water in proportion, adding them into a mixer, stirring, and mixing evenly to obtain a mixture A; (2) adding aluminum borate whiskers and nano-calcium carbonate to mixed material A, and stirring to obtain mixed material B; (3) Add fine aggregate, coarse aggregate and reinforcing fiber to mixture B and stir at high speed to obtain a mixed gel.
6. The method for preparing a bridge reinforcement carbon fiber-containing hybrid gel according to claim 5, characterized in that: In step (1), the stirring time is 1-3 min, and the stirring rate is 30-50 r / min.
7. The method for preparing a bridge reinforcement carbon fiber-containing hybrid gel according to claim 5, characterized in that: In step (2), the stirring time is 0.5-2 min, and the stirring rate is 30-50 r / min.
8. The method for preparing a bridge reinforcement carbon fiber-containing hybrid gel according to claim 5, characterized in that: In step (3), the stirring time is 1-2 min, and the stirring rate is 120-160 r / min.
Citation Information
Patent Citations
Engineered hybrid fibre reinforced ternary blend geopolymer concrete composite
AU2020102145A4